Higgs compositeness in Sp(2N) gauge theories — The pure gauge model - Biagio Lucini (EPJ Web of Conferences, 2018)
As a first step in the study of Sp(2N) composite Higgs models, we obtained aset of novel numerical results for the pure gauge Sp(4) lattice theory in 3+1 space-timedimensions. Results for the continuum extrapolations of the string tension and the glueballmass spectrum are presented and their values are compared with the same quantitiesin neighbouring SU(N) models.